ECOLOGICAL IMPACT OF THE CRAZY ANT, Paratrechina fulva (Mayr), IN THE CIMITARRA MUNICIPALITY (SANTANDER) - ZENNER DE POLANÍA, INGEBORG; MARTINEZ-WILCHES, ORLANDO (Revista Colombiana de Entomología, 1992)
The economic importance of the "hormiga loca", as a pest of household, domestic animals, and indirectly of agriculture, and as the cause of social problems, is well documented. its impact on the native fauna of the invaded areas, especially on other anis, is however unknown. To determine this aspect, collections, and observations of insects and some vertebrates were carried out during four periods in one year, at the municipality of Cimitarra (Santander, Colombia) For sampling purposes the area was divided into two ecological strata; within each, four localities were chosen and within each locality three collection sites were selected, corresponding to an area free of P. fulva, border of invasion and completely colonized. The data obtained were submitted to a two-way ANOVA, Duncan's multiple range test, furthermore Shannon's index of species diversity and richness was calculated. The results showed that the local fauna is evidently affected by the invasion of the "hormiga loca", decreasing the original species richness in 94.74%. Of a total of 38 ant species found, only Monomorium floricola (Jerdon) and Dolichoderus diversus Emery, survive in colonized areas. Seven soil-inhabiting insect species, the poisonous snake Micrurus sp.andthree species of lizards present in P. fulva free areas, were totally displaced. The diversity index of ant species calculated of 1.763318 for the P. fulva free areas, decrease to 0.008795 for invaded areas. As a whole, these data indicate the serious threat the "hormiga loca" constitutes to the biodiversity of arthropods and vertebrates living within and on the soil surface in a given area, and inclusive allow the inference that the invasion causes ecological changes, only revertible on a very long term base.